Rebel in the rye [videorecording (DVD)] - Strong, Danny, 1974-; Hoult, Nicholas, 1989-; Spacey, Kevin; Garber, Victor; Davis, Hope, 1967-; Slawenski, Kenneth (Shout! Factory, 2018)
The life of celebrated but reclusive author, J.D. Salinger, who gained worldwide fame with the publication of his novel, The Catcher in the Rye.